2021
DOI: 10.3892/ol.2021.13037
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI is useful for early detection of pelvic insufficiency fractures after radiotherapy for cervical cancer

Abstract: Radiotherapy (RT) is used to manage cervical cancer, and pelvic insufficiency fracture (PIF) is known as a late complication of RT. The present study identified risk factors for PIF after radiotherapy for cervical cancer, and investigated its incidence rate. It also considered the usefulness of positron emission tomography/magnetic resonance imaging (PET/MRI) in PIF diagnosis. A total of 149 patients with cervical cancer who received definitive or adjuvant RT with/without concurrent chemotherapy between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PET/MRI offers the advantage of its excellent anatomical resolution added to the functional study. PET/MRI was able to demonstrate the onset of a pelvic fracture in the context of irradiation earlier than PET/CT, 26 with the potential to allow early intervention.…”
Section: Future Perspectives In Posttreatment Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…PET/MRI offers the advantage of its excellent anatomical resolution added to the functional study. PET/MRI was able to demonstrate the onset of a pelvic fracture in the context of irradiation earlier than PET/CT, 26 with the potential to allow early intervention.…”
Section: Future Perspectives In Posttreatment Assessmentmentioning
confidence: 99%
“…The incidence of radiotherapy-induced pelvic insufficiency fractures was reported to be 2.7 to 89% in a 2018 systematic review, 1 with a reported incidence for sacral involvement of at least 20%. 26 In patients with osteoporosis, the risk of fracture after radiotherapy is increased (e.g., in postmenopausal women, with a prevalence of up to 34%). 27 Their configuration is typical, parallel to the sacroiliac joints, with ill-defined margins in all sequences.…”
Section: Insufficiency Fracturesmentioning
confidence: 99%
“…According to a survey report by the World Health Organization in 2018, the incidence and mortality of cervical cancer worldwide is related to the changes in China's social environmental factors as well as the improved diagnostic techniques. Currently, the number of patients who die each year due to cervical cancer in China is above 50,000, accounting for approximately 18.4% of all deaths from female malignancies [5,6], indicating that the disease is seriously endangering the life health of Chinese women. Performing treatment measures to patients according to clinical stages while actively detecting the treatment effect is key to improving the prognosis of cervical cancer, and in particular, the accuracy of staging in patients with moderate to advanced cervical cancer will directly affect the selection and formulation of treatment options for them.…”
Section: Introductionmentioning
confidence: 99%